Brain-sparing sympathofacilitators mitigate obesity without adverse cardiovascular effects - Mahú, Inês (2020)
© 2020 The Authors. Published by Elsevier Inc. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).